Which attributes are important for patrons of fine-dining restaurants? A choice-based conjoint analysis - Paritosh Dabral; Smitha Nayak; Senthilkumaran Piramanayagam (Cogent Business & Management)
With strong economic growth and shifting consumer aspirations, fine-dining in India has emerged as a rapidly growing segment of the food service industry. While several studies have explored dining experiences in global contexts, limited research exists on how Indian consumers make trade-offs across multiple restaurant attributes. This study applies Cue Utilisation Theory to classify and examine the influence of internal cues (e.g. food quality, service, ingredients) and external cues (e.g. price, online reviews, location) on consumer preferences. A choice-based conjoint experiment using the PAPRIKA method was conducted with 492 fine-dining patrons in a major Indian city. The results reveal that internal cues—especially food quality and service—have the strongest influence on restaurant selection, while external cues like price and online reviews are also significant, albeit secondary. These findings demonstrate the relative dominance of experience-based factors in hedonic, high-involvement consumption settings such as fine-dining.